Sensory Ataxia and Vitamin E Deficiency - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
A progressive limb and gait ataxia, distal loss of proprioception and vibration sense, and areflexia, caused by a prolonged and severe vitamin E deficiency, are reported in four patients evaluated as adults at King's College, Hammersmith Hospital, and Institutes of Neurology and Child Health, London, UK.